Statistics: concepts and applications - Pal, Nabendu; Sarkar, Sahadeb (New Delhi: Prentice-Hall of India, 2005)
This introductory-level book is designed as a text for students of statistics, mathematics, and management. In addition, postgraduate students pursuing courses in other subjects such as biology, psychology, sociology, and anthropology would also find the book extremely useful. The text gives a clear and concise analysis of the fundamental principles of statistics. In the process, it uses illustrative and motivating examples to make the concepts clearer and show how these concepts can be applied to real-world situations. This book, with its stress on the fundamental principles and reinforced by its illustrative approach, should appeal not only to students but also to practicing professionals, surveyors, and administrators.
Basic Concepts Of Statistical Studies -- Organizing A Raw Dataset -- Pictorial Representation Of A Dataset -- Summarizing A Raw Dataset -- Summarizing An Organized Dataset -- Concepts Of Probability -- Random Variables -- Binomial Experiments -- Normal Curve And Normal Distribution -- Applications of The Normal Distribution -- Estimation Of Population Parameters -- Hypothesis Testing For A Single Population -- Hypothesis Testing To Compare Two Populations -- Bivariate Quantitative Data : Correlation and Regression -- Bivariate Categorical Data : Contingency Tables -- Multinominal Experiments: Goodness of Fit Test -- Hypothesis Testing to Compare Multiple Populations -- Quality Management Using Statistics
Includes index
Keywords: Statistics; Statistical theory and methods; Management